PERBUATAN MELAWAN HUKUM DALAM KEPEMILIKANHAK MILIK ATAS TANAH YANG MENJADI OBYEKWAKAF (Studi Putusan Nomor 55/Pdt.G/2014/PN.SKH) - Aulia Mutiara Cintani, - (2019)
This study aims to determine whether the ownership rights to the land that is the object of the waqf that the defendant is doing is against the law and knows what legal consequences arise as a result of illegal acts committed by the defendant. The research method used is normative juridical research, namely research using library data originating from primary sources, secondary sources and tertiary sources that are analyzed descriptively.In this research the researcher discusses the unlawful acts carried out by a person on ownership of land ownership that is the object of waqf According to Article 1 Paragraph 1 of Law Number 41 of 2004 concerning Waqf, waqf is a legal act of wakif to separate or surrender part of property his property to be used forever or a certain period of time in accordance with his interests for worship and / or general welfare according to Sharia, while Act Against the Law (PMH) is any act that violates the law carried out by someone and because of the wrongdoing has caused harm to others. Land is one of the objects of waqf in Indonesia, there are many kinds of land rights in Indonesia, the land rights are regulated in Law Number 5 Year 1960 concerning the Agrarian Principles with the enactment of this Law, then revoke all provisions concerning land contained in the Civil Code except about mortgage rights. While the arrangement of land waqf is regulated further in Law Number 41 of 2004 concerning waqf.